Modeling and Design of a Plasmonic Sensor for High Sensing Performance and Clear Registration - Guoxiong Cai; Wei Li; Ying Chen; Na Liu; Zhengyong Song; Qing Huo Liu (IEEE Photonics Journal)
A plasmonic sensor based on the nano-cylinder photonic crystal slab is modeled and designed for the refractive index sensing application. Design considerations and sensor characteristics are explored in detail using the higher order accuracy spectral element method. The geometrical parameters of the designed plasmonic sensor are optimized. With the shallowly etched configuration and the small radius of the nano-cylinder, the sensor simultaneously achieves a high sensing performance of figure of merit $FoM=280$ and a clear registration of full-height/full-width at half-maximum $FH/FWHM=0.34\ nm^{-1}$ for the lattice period $P=750\ nm$ , the cylinder radius $r=85\ nm$ , and the cylinder thickness $t=125\ nm$ . The proposed plasmonic sensor can find its great potential for applications relying on detecting refractive index.